Uptake Quantification of Antigen Carried by Nanoparticles and Its Impact on Carrier Adjuvanticity Evaluation - Yupu Zhu; Minxuan Cui; Yutao Liu; Zhengjun Ma; Jiayue Xi; Yi Tian; Jinwei Hu; Chaojun Song; Li Fan; Quan Li (Vaccines, 2023)
Nanoparticles have been identified in numerous studies as effective antigen delivery systems that enhance immune responses. However, it remains unclear whether this enhancement is a result of increased antigen uptake when carried by nanoparticles or the adjuvanticity of the nanoparticle carriers. Consequently, it is important to quantify antigen uptake by dendritic cells in a manner that is free from artifacts in order to analyze the immune response when antigens are carried by nanoparticles. In this study, we demonstrated several scenarios (antigens on nanoparticles or inside cells) that are likely to contribute to the generation of artifacts in conventional fluorescence-based quantification. Furthermore, we developed the necessary assay for accurate uptake quantification. PLGA NPs were selected as the model carrier system to deliver EsxB protein (a Staphylococcus aureus antigen) in order to testify to the feasibility of the established method. The results showed that for the same antigen uptake amount, the antigen delivered by PLGA nanoparticles could elicit 3.6 times IL-2 secretion (representative of cellular immune response activation) and 1.5 times IL-12 secretion (representative of DC maturation level) compared with pure antigen feeding. The findings above give direct evidence of the extra adjuvanticity of PLGA nanoparticles, except for their delivery functions. The developed methodology allows for the evaluation of immune cell responses on an antigen uptake basis, thus providing a better understanding of the origin of the adjuvanticity of nanoparticle carriers. Ultimately, this research provides general guidelines for the formulation of nano-vaccines.